Hubungan Teman Sebaya Dengan Perilaku Merokok Pada Remaja Di Kp. Sawah Rt 01/03 Kelurahan Jatimelati, Kecamatan Pondok Melati - Isnaeni Isnaeni; Akbar Raja Segara (Universitas Pahlawan Tuanku Tambusai, 2026)
Background Adolescent smoking behavior is an ongoing public health problem influenced by social factors, particularly peer influence. Adolescence is a transitional phase characterized by a strong need for social acceptance, which often leads adolescents to adjust their behavior according to their peer group. Objective This study aimed to determine the relationship between peer influence and smoking behavior among adolescents in KP. Sawah RT 01/03, Jatimelati Village, Pondok Melati District. Methods This study employed a quantitative design with a descriptive-analytic approach using a cross-sectional method. The study population consisted of all adolescents in KP. Sawah RT 01/03, totaling 40 respondents, selected using a total sampling technique. Data were collected using a structured questionnaire measuring peer influence and smoking behavior variables. Data analysis was conducted using univariate and bivariate analysis with the Chi-Square test. Results All respondents (100%) were categorized as having high peer influence, defined as frequent interaction with peers, strong emotional closeness, and dominant peer group norms influencing daily behavior. Most respondents (75%) exhibited high-level smoking behavior, while 25% were categorized as moderate. The peer influence variable showed no variation, therefore, statistical association testing could not be performed. Conclusion and Recommendation Peer environments play a highly dominant role in adolescents’ social lives and have the potential to influence smoking behavior. It is recommended that healthcare professionals, families, and communities strengthen promotive and preventive efforts through healt education, youth group developmen, and the reinforcement of positive social environments to reduce smoking behavior among adolescents.